(untitled) (Research, Society and Development, 2024)
Temporal lobe epilepsy (TLE) is a common neurological syndrome characterized by refractory seizures, often associated with hippocampal sclerosis (HS). Understanding the inflammatory mechanisms in TLE is essential for developing more effective treatments, especially for cases that do not respond to conventional therapies. With the aim of investigating the relationship between neuroinflammation and TLE with HS, a systematic review was conducted following PRISMA guidelines, with a final sample of 10 articles from 2019 to 2024 available in the Virtual Health Library (VHL). The results showed that neuroinflammation, mediated by cytokines such as IL-1β, IL-6, and the protein HMGB1, exacerbates epileptic seizures. The activation of NLRP1 and NLRP3 inflammasomes, and the immune response of microglia and astrocytes, are linked to neuronal degeneration in the hippocampus. Neuroinflammation affects the integrity of hippocampal tissue, neurogenesis, and synaptic plasticity, leading to cognitive deficits. Thus, modulating inflammatory pathways emerges as a potential therapeutic strategy to reduce seizures and preserve cognitive function, but further studies are needed to optimize clinical management.